Nitrogen-rich fibrous carbon material as well as preparation method and application thereof
By modifying the lithium sulfur battery separator with nitrogen-rich fibrous carbon material, the shuttle effect of polysulfides is inhibited and the redox conversion of sulfur is accelerated, the problem of slow polysulfide shuttle effect and reaction kinetics in lithium sulfur batteries is solved. The cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411006817.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The shuttle effect of polysulfides in lithium-sulfur batteries leads to negative electrode corrosion and passivation, and the reaction kinetics of sulfur are slow, affecting the rate performance and cycle stability of the battery.
The lithium-sulfur battery separator is modified by using nitrogen-rich fibrous carbon materials. By doping nitrogen atoms into the carbon material, it improves its electrocatalytic capacity and adsorption capacity, inhibits the shuttle effect of polysulfides, and accelerates the redox of sulfur. Conversion rate.
It effectively improves the cycle stability and Coulomb efficiency of lithium-sulfur batteries, enhances the rate performance and sulfur utilization efficiency of the battery, and extends the cycle life of the battery.
Smart Images

Figure CN119145089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon material preparation and lithium-sulfur battery, and specifically relates to a nitrogen-rich fibrous carbon material and a preparation method and application thereof. Background Art
[0002] With the rapid development of high-mileage electric vehicles and smart grids, new requirements are being put forward for the energy density and cycle life of secondary batteries. Existing lithium-ion batteries are limited by their low theoretical specific capacity and high application cost of the positive electrode and are difficult to meet the development needs of future large-scale power-consuming equipment. Among all the newly developed battery systems, lithium-sulfur batteries stand out due to their ultra-high theoretical specific capacity (1675mAh g-1) and energy density (2600Wh kg-1), becoming the most promising next-generation lithium battery technology.
[0003] However, there are some thorny problems in the positive electrode of lithium-sulfur batteries that limit their practical application, including: (1) polysulfide, the intermediate product of lithium-sulfur battery discharge, will dissolve in the electrolyte and pass through the separator to the negative electrode surface during charging, causing irreversible loss of active substances and corrosion and passivation of the negative electrode surface; (2) sulfur and the final reaction product lithium sulfide have extremely poor electronic conductivity, resulting in slow sulfur reaction kinetics and ultimately affecting the battery's rate performance; (3) the different densities of lithium sulfide and sulfur will cause the volume of the positive electrode to change continuously during the battery cycle, causing damage to the positive electrode structure and the shedding of active substances, affecting the battery's cycle stability.
[0004] In order to improve the above problems, researchers modified the diaphragm, mainly by introducing functional coating materials on the diaphragm. These functional materials are usually carbon materials with high specific surface area and high conductivity, such as porous carbon, graphene and carbon nanotubes, etc. However, the interaction between non-polar carbon materials and polar polysulfides is weak, and polysulfides cannot be effectively fixed. Introducing heteroatoms into functional materials is one of the methods to improve the surface polarity of carbon materials. Among them, the doping of nitrogen atoms can give carbon materials good electrocatalytic ability, thereby accelerating the redox conversion rate of sulfur and improving the performance of lithium-sulfur batteries. Summary of the invention
[0005] In order to solve the problems existing in lithium-sulfur batteries in the prior art, the present invention provides a nitrogen-rich fibrous carbon material and a preparation method and application thereof. First, a nitrogen-rich fibrous carbon material is prepared, and then the nitrogen-rich fibrous carbon material is used to modify the diaphragm of the lithium-sulfur battery, which can effectively inhibit the shuttle effect of polysulfides and improve the long-cycle stability and coulombic efficiency of the lithium-sulfur battery.
[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions: a nitrogen-rich fibrous carbon material, characterized in that the carbon material has a variety of microscopic morphologies such as fibrous, layered, and porous, and the nitrogen-rich nitrogen structure includes pyridine N, pyrrole N, graphite N and NO structure.
[0007] Preferably, the nitrogen atom content is as high as 20.38%.
[0008] The invention also protects a preparation method of the nitrogen-rich fibrous carbon material, which is prepared by a step-by-step pyrolysis method using gelatin as a carbon source and graphitized carbon nitride as a soft template.
[0009] Preferably, the preparation method comprises the following steps:
[0010] 1) mechanically blending melamine and gelatin to obtain a nitrogen-rich fibrous carbon material precursor;
[0011] 2) The precursor obtained in step 1) is first dried, and then subjected to step-by-step pyrolysis treatment under a protective atmosphere to finally obtain a nitrogen-rich fibrous carbon material.
[0012] Preferably, in step 1), the mass ratio of melamine to gelatin is 5 to 40:1, and after mixing, the mixture is added to an appropriate amount of ethanol and ball milled with a ball mill at a speed of 200 to 500 r min -1 , the blending time is 3 to 10 hours.
[0013] Preferably, in step 2), the drying is performed by placing the mixture in a vacuum oven for 6 to 24 hours; and then drying the mixture in a nitrogen atmosphere at 1 to 3 °C min -1 The heating rate is raised to 400℃ and kept at this temperature for 1-2h, then heated at 5-10℃min -1 The heating rate is increased to 800°C and kept warm for 1 to 2 hours. After the insulation is completed, the temperature is naturally lowered to room temperature, and a nitrogen-rich fibrous carbon material is obtained after grinding.
[0014] Gelatin is a biomacromolecule rich in carbon atoms and polar functional groups. Using gelatin as an organic carbon source can prepare heteroatom-rich carbon materials. However, due to the soft texture of biomacromolecules, although the gelatin molecules themselves are fibrous, the carbon materials prepared by simple pyrolysis are very prone to agglomeration, resulting in the inability to retain the original fibrous structure of the gelatin molecules, thus losing the advantages of gelatin. Therefore, it is extremely difficult to prepare biomass carbon with a microscopic morphology of fibrous. The present invention unexpectedly found that it is very effective to use the layered two-dimensional material graphitized carbon nitride rich in nitrogen atoms as a soft template and nitrogen source to maintain the fibrous structure of gelatin itself, thereby preparing a carbon material with a high specific surface area and rich nitrogen doping with a fibrous microstructure. Using this material to modify the lithium-sulfur battery separator can effectively inhibit the polysulfide shuttle effect, promote the redox conversion of sulfur species, and improve the electrochemical performance of lithium-sulfur batteries.
[0015] The present invention also protects the application of the nitrogen-rich fibrous carbon material in electrochemical energy storage.
[0016] Preferably, the specific application scenarios include positive electrodes of lithium-sulfur batteries, separator coatings of lithium-sulfur batteries, negative electrodes of lithium-ion batteries, and electrodes of supercapacitors.
[0017] The present invention also protects a modified diaphragm, comprising a diaphragm and a modified coating arranged on the surface of the diaphragm; the components of the modified coating include a conductive agent, an adhesive and the nitrogen-rich fibrous carbon material described in the above scheme.
[0018] Preferably, the mass ratio of the nitrogen-rich fibrous carbon material, the conductive agent and the binder is 1 to 3:1 to 3:1.
[0019] The present invention also protects a method for preparing the modified diaphragm, comprising the following steps:
[0020] The nitrogen-rich fibrous carbon material is mixed with a conductive agent, a binder and a solvent in the above-mentioned proportion to obtain a nitrogen-rich fibrous carbon material slurry;
[0021] The nitrogen-rich fibrous carbon material slurry is coated on the surface of a commercial diaphragm and then dried to obtain a modified diaphragm.
[0022] The present invention also protects a lithium-sulfur battery, comprising a metal lithium negative electrode sheet, a sulfur positive electrode sheet, a diaphragm and an electrolyte, wherein the diaphragm is a modified diaphragm prepared by the above preparation method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a method for preparing a nitrogen-rich fibrous carbon material, using gelatin as a carbon source and graphitized carbon nitride as a soft template, and adopting a step-by-step pyrolysis method to prepare a nitrogen-rich fibrous carbon material. Graphitized carbon nitride can maintain a relatively stable state below 600°C, but will decompose into nitrogen-containing gas above 700°C and emit into the atmosphere with the circulating airflow, while inhibiting the carbon material from agglomerating into blocks. As the proportion of graphitized carbon nitride increases, the carbon material finally obtained will present a more obvious fibrous microstructure and a larger specific surface area. Due to the extremely high nitrogen content in graphitized carbon nitride, under the condition of co-pyrolysis with gelatin, some nitrogen atoms can be doped into the gelatin carbon material, giving it stronger adsorption and catalytic properties.
[0025] The present invention also provides the use of nitrogen-rich fibrous carbon materials in lithium-sulfur batteries. The highly conductive network of the nitrogen-rich fibrous carbon materials can accelerate the transmission speed of electrons and improve the utilization efficiency of sulfur. In addition, the nitrogen-rich fibrous carbon materials contain a large number of nitrogen atoms and oxygen atoms, so the nitrogen-rich fibrous carbon materials exhibit a strong adsorption capacity for polysulfides. In addition, the abundant nitrogen atoms and other heteroatoms from gelatin itself in the nitrogen-rich fibrous carbon materials give them high electrocatalytic activity to promote the redox conversion of sulfur species. Therefore, using nitrogen-rich fibrous carbon materials as multifunctional diaphragm coating materials can effectively improve the rate performance and cycle stability of lithium-sulfur batteries. The initial discharge capacity of a lithium-sulfur battery using a diaphragm modified with nitrogen-rich fibrous carbon materials at a current density of 1C is 1060mAh g -1 , and can still maintain 843mAh g after 200 cycles -1 The reversible capacity of the battery is about 80%, and the capacity retention rate is about 80%. In contrast, due to the severe polysulfide shuttle effect and slow redox kinetics, the discharge capacity of the lithium-sulfur battery assembled with a commercial separator is only 582 mAh g after 200 cycles at 1C. -1 , showing lower sulfur utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The following is a further description with reference to the accompanying drawings.
[0027] Figure 1 This is the SEM image of the nitrogen-rich fibrous carbon material prepared in Example 1.
[0028] Figure 2 This is a comparison chart of the discharge specific capacity and coulombic efficiency of the lithium-sulfur battery assembled with the modified diaphragm and the ordinary diaphragm at 1C current density in Example 1.
[0029] Figure 3 This is the SEM image of the nitrogen-rich fibrous carbon material prepared in Example 3. DETAILED DESCRIPTION
[0030] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0031] The gelatin particles are crushed by a pulverizer and then sieved to obtain gelatin particles with a smaller particle size, which is conducive to full mixing with melamine. The speed of the pulverization is 10000-50000 r min -1 The crushing time is 2 to 10 minutes; the aperture of the sieve is 0.03 to 0.018 mm, and the sieved material is gelatin particles with smaller particle size.
[0032] The present invention has no special requirements for the gelatin, and common gelatin can be used, specifically industrial gelatin, cowhide gelatin, pigskin gelatin, etc.
[0033] Accurately weigh 5-40g of melamine and 1g of gelatin particles, place them in a clean and dry ball mill, add 10-20mL of anhydrous ethanol, and place them in a ball mill for 3-8h. After the ball milling is completed, place the ball mill in a forced air drying oven at 40-60℃ and dry for 4-12h. After waiting for complete drying, transfer the dry powder to a crucible.
[0034] The crucible containing the dry powder was heated and carbonized in a tube furnace under a nitrogen atmosphere. The heating process was divided into two steps. The first step was to heat the crucible at 1-3 °C min -1 The heating rate is 5-8℃min. -1 The crucible was taken out after the temperature was naturally cooled to 30°C at a heating rate of 100 °C. The powder in the crucible was transferred to a mortar, ground, collected and stored, and finally a nitrogen-rich fibrous carbon material was obtained.
[0035] The present invention also provides a modified diaphragm, comprising a diaphragm and a modified layer arranged on the surface of the diaphragm; the components of the modified layer include a conductive agent, an adhesive and the nitrogen-rich fibrous carbon material described in the above scheme.
[0036] Preferably, the mass ratio of the nitrogen-rich fibrous carbon material, the conductive agent acetylene black and the adhesive polyvinylidene fluoride is 1 to 3:1 to 3:1.
[0037] The present invention also provides a method for preparing the modified diaphragm described in the above scheme, comprising the following steps:
[0038] The nitrogen-rich fibrous carbon material prepared above is mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 1 to 3:1 to 3:1, and N-methylpyrrolidone (NMP) is used as a solvent. The addition of the solvent makes the mass concentration of polyvinylidene fluoride in the slurry be 1 to 3wt%. All components are accurately weighed into a sample bottle with a magnet according to the proportion, and placed on a magnetic stirrer for stirring for 24 hours to finally obtain a uniformly dispersed slurry.
[0039] The slurry prepared above is coated on the surface of the commercial battery separator with a coater having a thickness of 60 to 150 μm. The coated separator is placed in a fume hood to dry naturally at room temperature for 12 to 24 hours, and then transferred to a vacuum drying oven for drying for 12 to 24 hours to ensure that all solvents are volatilized, and the drying temperature is 40 to 60°C. After complete drying, the separator is cut into discs with a diameter of 6 to 19 mm using a cutting machine.
[0040] The present invention also provides a lithium-sulfur battery, comprising a metal lithium negative electrode sheet, a sulfur positive electrode sheet, a diaphragm and an electrolyte, wherein the diaphragm is the modified diaphragm described in the above scheme or the modified diaphragm prepared by the preparation method described in the above scheme.
[0041] In the present invention, the preparation method of the sulfur positive electrode sheet is preferably: sublimated sulfur, conductive agent acetylene black and gelatin solution are mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on the surface of aluminum foil and then dried and pressed to finally obtain a sulfur positive electrode sheet; the mass fraction of the gelatin solution is preferably 1-5%, and the solvent is water; the mass ratio of the sublimated sulfur, conductive agent acetylene black and gelatin is preferably 63:30:7; the mixing method is preferably mechanical mixing; the sulfur loading on the surface of the aluminum foil is preferably 1.000-1.500 mg cm -2 The drying temperature is preferably 60°C, and the drying time is preferably 6 to 24 hours; the sulfur cathode sheet is preferably a disc with a diameter of 10 to 15 mm.
[0042] In the present invention, the electrolyte is preferably a mixed solvent of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME), and the volume ratio of DOL and DME in the mixed solvent is preferably 1:1; the solute is preferably lithium bistrifluoromethanesulfonyl imide (LiTFSI) and lithium nitrate (LiNO3), and the concentration of LiTFSI in the electrolyte is preferably 1M, and the concentration of LiNO3 is preferably 0.4M.
[0043] In a specific embodiment of the present invention, the metal lithium negative electrode sheet, the sulfur positive electrode sheet, the separator and the electrolyte are preferably assembled into a button battery, the obtained button battery is left to stand for 8 hours, and then a charge and discharge cycle test is performed at a current density of 1C.
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The commercial battery separator used in the examples is Celgard 2325.
[0046] Example 1
[0047] (1) Preparation of nitrogen-rich fibrous carbon materials:
[0048] Accurately weigh 10g of melamine and 1g of gelatin particles, place them in a clean and dry ball mill, add 10mL of anhydrous ethanol, and place them in a ball mill for 5 hours. After the ball milling is completed, place the ball mill in a forced air drying oven at 60°C and dry for 12 hours. After waiting for complete drying, transfer the dry powder to a crucible.
[0049] The crucible containing the dry powder was carbonized in a tube furnace under a nitrogen atmosphere. The heating process was divided into two steps. The first step was to heat the crucible at 2 °C min -1 The heating rate was 5℃min to 400℃ and kept at this temperature for 1h. -1 The crucible was taken out after the temperature was naturally cooled to 30°C at a heating rate of 100 °C. The powder in the crucible was transferred to a mortar, ground, collected and stored, and finally a nitrogen-rich fibrous carbon material was obtained.
[0050] Figure 1 This is a scanning electron microscope (SEM) image of the nitrogen-rich fibrous carbon material prepared in this example. It can be seen from the image that the microscopic morphology of the obtained material is fibrous.
[0051] (2) Preparation of modified diaphragm:
[0052] The nitrogen-rich fibrous carbon material prepared above was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 2:2:1, and N-methylpyrrolidone (NMP) was used as a solvent. The addition of the solvent made the mass concentration of polyvinylidene fluoride in the slurry 1.5wt%. All components were accurately weighed into a sample bottle with a magnet according to the proportion, placed on a magnetic stirrer and stirred for 24 hours, and finally a uniformly dispersed slurry was obtained.
[0053] The slurry prepared above was coated on the surface of the commercial battery separator with a coater having a thickness of 60 μm. The coated separator was placed in a fume hood and dried naturally at room temperature for 12 hours, and then transferred to a vacuum drying oven for drying for 12 hours to ensure that all solvents were volatilized. The drying temperature was 60°C. After complete drying, the separator was cut into discs with a diameter of 19 mm using a cutting machine.
[0054] (3) Assembling lithium-sulfur batteries
[0055] The above-mentioned diaphragm, common metal lithium negative electrode, and sulfur positive electrode were assembled into a button battery in a glove box protected by argon environment. The battery shell model was CR2025, and the electrolyte was DOL / DME=1:1Vol%+1MLiTFSI+0.4M LiNO3. The assembled battery was left to stand for 8h. Similarly, a commercial battery diaphragm, lithium metal negative electrode, and sulfur positive electrode were assembled into a lithium-sulfur battery as a control.
[0056] Among them, the preparation method of the sulfur positive electrode sheet is: mechanically mix sublimated sulfur, conductive carbon black and gelatin solution in a mass ratio of 63:30:7, with a gelatin mass concentration of 2% to obtain a slurry, which is coated on a clean aluminum foil, and the aluminum foil coated with the slurry is shade-dried at room temperature for 1 hour, and the shade-dried aluminum foil is placed in a vacuum oven at 60°C and dried for 24 hours, then taken out, and the completely dried aluminum foil with the positive electrode coating is cut into discs with a diameter of 12 mm using a cutting machine.
[0057] (4) Electrochemical performance test of lithium-sulfur batteries
[0058] The lithium-sulfur battery was tested for cycle performance on a charge-discharge device under 1C test conditions. The test results are as follows: Figure 2 shown.
[0059] Figure 2 This is a comparison chart of the discharge specific capacity and coulombic efficiency of lithium-sulfur batteries assembled using modified diaphragms and commercial diaphragms.
[0060] Depend on Figure 2 It can be seen from the data that the lithium-sulfur battery assembled using the modified diaphragm prepared by the present invention has a higher discharge specific capacity and a more stable cycle efficiency than the lithium-sulfur battery assembled using the commercial diaphragm, indicating that the use of the nitrogen-rich fibrous carbon material of the present invention to modify the commercial diaphragm can effectively inhibit the shuttle effect of polysulfides and effectively improve the capacity and cycle stability of the lithium-sulfur battery.
[0061] Example 2
[0062] (1) Preparation of nitrogen-rich fibrous carbon materials:
[0063] Accurately weigh 10g of melamine and 1g of gelatin particles, place them in a clean and dry ball mill, add 10mL of anhydrous ethanol, and place them in a ball mill for 5 hours. After the ball milling is completed, place the ball mill in a forced air drying oven at 60°C and dry for 12 hours. After waiting for complete drying, transfer the dry powder to a crucible.
[0064] The crucible containing the dry powder was carbonized in a tube furnace under a nitrogen atmosphere. The heating process was divided into two steps. The first step was to heat the crucible at 2 °C min -1 The heating rate was 5℃min to 400℃ and kept at this temperature for 1h. -1 The crucible was taken out after the temperature was naturally cooled to 30°C at a heating rate of 100 °C. The powder in the crucible was transferred to a mortar, ground, collected and stored, and finally a nitrogen-rich fibrous carbon material was obtained.
[0065] (2) Preparation of modified diaphragm:
[0066] The nitrogen-rich fibrous carbon material prepared above was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 2:2:1, and N-methylpyrrolidone (NMP) was used as a solvent. The addition of the solvent made the mass concentration of polyvinylidene fluoride in the slurry 1.5wt%. All components were accurately weighed into a sample bottle with a magnet according to the proportion, placed on a magnetic stirrer and stirred for 24 hours, and finally a uniformly dispersed slurry was obtained.
[0067] The slurry prepared above was coated on the surface of the commercial battery separator with a coater having a thickness of 60 μm. The coated separator was placed in a fume hood and dried naturally at room temperature for 12 hours, and then transferred to a vacuum drying oven for drying for 12 hours to ensure that all solvents were volatilized. The drying temperature was 60°C. After complete drying, the separator was cut into discs with a diameter of 19 mm using a cutting machine.
[0068] (3) Assembling lithium-sulfur batteries
[0069] The above-mentioned diaphragm, common metal lithium negative electrode, and sulfur positive electrode were assembled into a button battery in a glove box protected by argon environment. The battery shell model was CR2025, and the electrolyte was DOL / DME=1:1Vol%+1MLiTFSI+0.4M LiNO3. The assembled battery was left to stand for 8h. Similarly, a commercial battery diaphragm, lithium metal negative electrode, and sulfur positive electrode were assembled into a lithium-sulfur battery as a control.
[0070] Among them, the preparation method of the sulfur positive electrode sheet is: mechanically mix sublimated sulfur, conductive carbon black and gelatin solution in a mass ratio of 63:30:7, with a gelatin mass concentration of 2% to obtain a slurry, which is coated on a clean aluminum foil, and the aluminum foil coated with the slurry is shade-dried at room temperature for 1 hour, and the shade-dried aluminum foil is placed in a vacuum oven at 60°C and dried for 24 hours, then taken out, and the completely dried aluminum foil with the positive electrode coating is cut into discs with a diameter of 12 mm using a cutting machine.
[0071] (4) Electrochemical performance test of lithium-sulfur batteries
[0072] The cycle performance test of the lithium-sulfur battery was carried out on the charging and discharging equipment, and the test condition was 4C. It can be seen from the test results that the lithium-sulfur battery assembled using the modified diaphragm prepared by the present invention has a higher discharge specific capacity and a more stable cycle efficiency than the lithium-sulfur battery assembled using the commercial diaphragm, indicating that the commercial diaphragm modified by the nitrogen-rich fibrous carbon material of the present invention can effectively inhibit the shuttle effect of polysulfides and effectively improve the capacity and cycle stability of the lithium-sulfur battery.
[0073] Example 3
[0074] (1) Preparation of nitrogen-rich fibrous carbon materials:
[0075] Accurately weigh 20g of melamine and 1g of gelatin particles, place them in a clean and dry ball mill, add 10mL of anhydrous ethanol, and place them in a ball mill for 5h. After the ball milling is completed, place the ball mill in a forced air drying oven at 60℃ and dry for 12h. After waiting for complete drying, transfer the dry powder to a crucible.
[0076] The crucible containing the dry powder was carbonized in a tube furnace under a nitrogen atmosphere. The heating process was divided into two steps. The first step was to heat the crucible at 2 °C min -1 The heating rate was 5℃min to 400℃ and kept at this temperature for 1h. -1 The crucible was taken out after the temperature was naturally cooled to 30°C at a heating rate of 100 °C. The powder in the crucible was transferred to a mortar, ground, collected and stored, and finally a nitrogen-rich fibrous carbon material was obtained.
[0077] Figure 3 This is a scanning electron microscope (SEM) image of the nitrogen-rich fibrous carbon material prepared in this example. It can be seen from the image that the microscopic fibrous morphology of the obtained material is more obvious.
[0078] (2) Preparation of modified diaphragm:
[0079] The nitrogen-rich fibrous carbon material prepared above was mixed with the conductive agent acetylene black and the binder polyvinylidene fluoride in a mass ratio of 2:2:1, and N-methylpyrrolidone (NMP) was used as a solvent. The addition of the solvent made the mass concentration of polyvinylidene fluoride in the slurry 1.5wt%. All components were accurately weighed into a sample bottle with a magnet according to the proportion, placed on a magnetic stirrer and stirred for 24 hours, and finally a uniformly dispersed slurry was obtained.
[0080] The slurry prepared above was coated on the surface of the commercial battery separator with a coater having a thickness of 60 μm. The coated separator was placed in a fume hood and dried naturally at room temperature for 12 hours, and then transferred to a vacuum drying oven for drying for 12 hours to ensure that all solvents were volatilized. The drying temperature was 60°C. After complete drying, the separator was cut into discs with a diameter of 19 mm using a cutting machine.
[0081] (3) Assembling lithium-sulfur batteries
[0082] The above-mentioned diaphragm, common metal lithium negative electrode, and sulfur positive electrode were assembled into a button battery in a glove box protected by argon environment. The battery shell model was CR2025, and the electrolyte was DOL / DME=1:1Vol%+1MLiTFSI+0.4M LiNO3. The assembled battery was left to stand for 8h. Similarly, a commercial battery diaphragm, lithium metal negative electrode, and sulfur positive electrode were assembled into a lithium-sulfur battery as a control.
[0083] Among them, the preparation method of the sulfur positive electrode sheet is: mechanically mix sublimated sulfur, conductive carbon black and gelatin solution in a mass ratio of 63:30:7, with a gelatin mass concentration of 2% to obtain a slurry, which is coated on a clean aluminum foil, and the aluminum foil coated with the slurry is shade-dried at room temperature for 1 hour, and the shade-dried aluminum foil is placed in a vacuum oven at 60°C and dried for 24 hours, then taken out, and the completely dried aluminum foil with the positive electrode coating is cut into discs with a diameter of 12 mm using a cutting machine.
[0084] (4) Electrochemical performance test of lithium-sulfur batteries
[0085] The lithium-sulfur battery was subjected to a cycle performance test on a charge and discharge device, and the test condition was 1C. The test results show that the lithium-sulfur battery assembled using the modified diaphragm prepared by the present invention has a higher discharge specific capacity and a more stable cycle efficiency than the lithium-sulfur battery assembled using the commercial diaphragm, indicating that the commercial diaphragm modified by the nitrogen-rich fibrous carbon material of the present invention can effectively inhibit the shuttle effect of polysulfides and effectively improve the capacity and cycle stability of the lithium-sulfur battery.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and perfections without departing from the principle of the present invention. These improvements and perfections should also be regarded as within the scope of protection of the present invention.
Claims
1. A nitrogen-rich fibrous carbon material, characterized in that The carbon material has a variety of microscopic morphologies including fibrous, layered and porous. The nitrogen-rich nitrogen structure includes pyridinic N, pyrrolic N, graphitic N and NO structure.
2. The nitrogen-rich fibrous carbon material according to claim 1, characterized in that The nitrogen atomic content is as high as 20.38%.
3. The method for preparing a nitrogen-rich fibrous carbon material according to claim 1 or 2, characterized in that: It was prepared by a step-by-step pyrolysis method using gelatin as the carbon source and graphitized carbon nitride as the soft template.
4. The preparation method according to claim 3, characterized in that: The following steps are involved: 1) mechanically blending melamine and gelatin to obtain a nitrogen-rich fibrous carbon material precursor; 2) The precursor obtained in step 1) is first dried, and then subjected to step-by-step pyrolysis treatment under a protective atmosphere to finally obtain a nitrogen-rich fibrous carbon material.
5. The preparation method according to claim 4, characterized in that: In step 1), the mass ratio of melamine to gelatin is 5 to 40:
1. After mixing, the mixture is added to an appropriate amount of ethanol and ball milled with a ball mill at a speed of 200 to 500 r min. -1 , the blending time is 3 to 10 hours.
6. The preparation method according to claim 4, characterized in that: In step 2), the drying step is performed by placing the mixture in a vacuum oven for 6 to 24 hours; and then drying the mixture in a nitrogen atmosphere at 1 to 3 °C min -1 The heating rate is raised to 400℃ and kept at this temperature for 1-2h, then heated at 5-10℃min -1 The heating rate is raised to 800°C and kept warm for 1 to 2 hours. After the insulation is completed, the temperature is naturally lowered to room temperature, and a nitrogen-rich fibrous carbon material is obtained after grinding.
7. Application of the nitrogen-rich fibrous carbon material according to any one of claims 1-2 or the nitrogen-rich fibrous carbon material prepared by the preparation method according to any one of claims 3-6 in electrochemical energy storage, and specific application occasions include positive electrodes of lithium-sulfur batteries, lithium-sulfur battery diaphragm coatings, negative electrodes of lithium-ion batteries, and electrodes of supercapacitors.
8. A modified diaphragm, characterized in that: It comprises a diaphragm and a modified coating disposed on the surface of the diaphragm; The components of the modified coating include a conductive agent, a binder and a nitrogen-rich fibrous carbon material, and the nitrogen-rich fibrous carbon material is the nitrogen-rich fibrous carbon material described in any one of claims 1-2 or the nitrogen-rich fibrous carbon material prepared by the preparation method described in any one of claims 3-6; the mass ratio of the nitrogen-rich fibrous carbon material, the conductive agent and the binder is 1 to 3:1 to 3:
1.
9. The method for preparing the modified diaphragm according to claim 8, characterized in that: The following steps are involved: The nitrogen-rich fibrous carbon material is mixed with a conductive agent, a binder and a solvent in the above-mentioned proportion to obtain a nitrogen-rich fibrous carbon material slurry; The nitrogen-rich fibrous carbon material slurry is coated on the surface of a commercial diaphragm and then dried to obtain a modified diaphragm.
10. A lithium-sulfur battery, characterized in that: The invention comprises a metal lithium negative electrode sheet, a sulfur positive electrode sheet, a diaphragm and an electrolyte, wherein the diaphragm is the modified diaphragm according to claim 8 or the modified diaphragm prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Lithium-sulfur battery diaphragm based on functional carbon material as well as preparation method and application of lithium-sulfur battery diaphragm
CN115513605A
Collagen-based fibrous carbon-hydroxyapatite nano composite material as well as preparation method and application thereof
CN116315419A
